Pengaruh Filler Nano Precipitated Calcium Carbonate dan Gliserol Terhadap Bioplastik Pati Jagung - , Resa Damayanti; Meldi Ramahdani Intan Pertiwi; Titi Susilowati; Caecilia Pujiastuti; Susilowati (Jurnal Serambi Engineering, 2025)
Precipitated calcium carbonate (PCC) with a size of less than 100 nm has been shown to improve the hardness and strength of a material, making it suitable as a filler in the production of bioplastics. Biodegradable plastics are plastics that can be used like conventional plastics, but can be broken down by microorganisms after use, making them environmentally friendly. The aim of this study is to investigate the effect of adding nanoprecipitated calcium carbonate (PCC) filler and glycerol on the mechanical properties and biodegradation of corn starch-based bioplastics, and to produce biodegradable plastic that meets the Indonesian National Standard (SNI). The method used is melt intercalation to produce bioplastics from corn starch with the addition of nano-PCC and glycerol. The best results were obtained with 12% Nano-PCC and 20% glycerol, which gave a tensile strength of 3.54 MPa, 12% Nano-PCC and 50% glycerol, which gave an elongation percentage of 23.7%, and 4% Nano-PCC and 60% glycerol, which gave 100% biodegradation within 30 days. A higher concentration of Nano-PCC filler increases the tensile strength, improves the elongation percentage and reduces the degradation rate of the plastic. A higher concentration of glycerol decreases tensile strength, increases elongation and increases the degradation rate of the plastic.